From Disarmament to Rearmament : The Reversal of US Policy toward West Germany, 1946-1955 - Goldberg, Sheldon A. (Book collections on Project MUSE., 2017)
At the end of World War II, the Allies were unanimous in their determination to disarm the former aggressor Germany. As the Cold War intensified, however, the decision whether to reverse that policy and to rearm West Germany led to disagreements both within the U.S. government and among members of the nascent NATO alliance.